2021
DOI: 10.1177/15554120211039082
|View full text |Cite
|
Sign up to set email alerts
|

Online Gaming and Racism: Impact on Psychological Distress Among Black, Asian, and Latinx Emerging Adults

Abstract: Although online racism occurs frequently and explicitly in online gaming (e.g., anti-Black hate speeches), no research has examined the psychological impact on racial/ethnic minority players. Thus, the current study examined the mediating role of online racism in the link between time spent in online gaming and psychological distress. Using data from 765 racial minority emerging adults in the United States and with gender controlled, time spent in online gaming predicted greater exposure to online racism, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Studies have shown that various racial groups have experienced discrimination online due to their race or ethnicity [ 36 - 40 ], and this discrimination has continued throughout the COVID-19 pandemic [ 41 - 43 ]. During the COVID-19 pandemic, Asian Americans and people of Asian ethnic origin have become particularly vulnerable to racial discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that various racial groups have experienced discrimination online due to their race or ethnicity [ 36 - 40 ], and this discrimination has continued throughout the COVID-19 pandemic [ 41 - 43 ]. During the COVID-19 pandemic, Asian Americans and people of Asian ethnic origin have become particularly vulnerable to racial discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tynes et al [ 37 ] found that Black students and other adolescents of color were subjected to both vicarious and individual forms of online racial discrimination, which impacted students’ psychological functioning. In addition, both online vicarious and individual discrimination were significantly associated with worse psychological well-being among adults of racial/ethnic minorities (eg, Black Americans, Latinx Americans, Asian Americans) [ 34 , 35 , 39 , 40 ]. To our knowledge, existing research has only focused on the impacts of offline forms of racial discrimination in the context of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the majority of previous studies focused on children and youth (e.g., Ginsburg et al, 2007 ; Yogman et al, 2018 ) or on electronic play (e.g., Müller and Bonnaire, 2021 ; TaeHyuk Keum and Hearns, 2022 ). In the present study, most emerging adults spent less than 7 h weekly on play/extracurricular activities (80%) and leisure reading (93%) in the last 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Online racial discrimination can be individual (i.e., personally directed at an individual online) or vicarious (i.e., witnessed online). Exposure to racially discriminatory content online is associated with worse mental health and lower self-esteem both for adolescents (e.g., Motley et al, 2020; Tynes et al, 2019) and for emerging adults (e.g., Keum & Hearns, 2022; Keum & Miller, 2017; Maxie-Moreman & Tynes, 2022; Volpe et al, 2020). It may be that some uses of Twitter are associated with more exposure to online racial discrimination.…”
Section: Features Of Emerging Adulthoodmentioning
confidence: 99%